Caudal vs Transforaminal Epidural Steroid Injections as Short‐Term (6 Months) Pain Relief in Lumbar Spinal Stenosis Patients with Sciatica. Issue 3 (16th December 2013) - Ploumis, Avraam; Christodoulou, Pavlos; Wood, Kirkham B.; Varvarousis, Dimitrios; Sarni, James L.; Beris, Alexander
Abstract Objective The aim of this study is to evaluate prospectively the efficacy of caudal epidural steroid injection (CESI) and transforaminal epidural steroid injection (TFESI) in lumbar spinal stenosis patients with sciatic pain. Design Prospective clinical study. Setting and Patients Thirty‐one patients (average age 62 years) from two hospitals, with single dermotomal distribution of sciatic pain due to spinal stenosis were included in the study. Interventions Patients underwent epidural steroid injections done by the same injectionist. Eleven patients from one hospital were included in the CESI group, while the TFESI group consisted of 20 comparable patients from the second site. Outcome Measures Primary outcome measure was the complete relief or at least 50% reduction of pain (visual analog scale [VAS]) at 6 months postinjection. Secondary outcome measures were the improvement of function (of at least 15 points of Oswestry Disability Index [ODI]) at 6 months and the changes of VAS and ODI and at 2 weeks, at 3 months, and at 6 months postinjection. Results A significantly greater number of stenosis patients showed pain relief at 6 months postinjection with TFSI (90%) than with CESI (54.54%). All patients with TFSI showed improvement of function at 6 months while only three (27.27%) patients with caudal epidural improved functionally. Out of the total 31 patients, two patients from group A underwent a second CESI at 15 days postinjection and decompressive spine surgery between 3 and 6 months postinjection. Conclusions The effectiveness of transforaminal steroid injection for the stenosis patients with sciatica was superior to caudal at 6 months postinjection.